Analysis of the Spatial Distribution of Detector Sensitivity in a Multilayer Randomly Inhomogeneous Medium with Strong Light Scattering and Absorption by the Monte Carlo Method. - Meglinski, I. V.; Matcher, S. J. (Springer Science Business Media, 2001)
The spatial distribution of sensitivity in the domain of detection of a fiber- optic sensor used for spectrophotometric studies of skin and other biological tissues is studied. The method and results of modeling the propagation of optical radiation in multilayer randomly inhomogeneous media with strong light scattering and absorption are presented. Owing to the small distances between the source and detector (100–800 µm), the propagation of radiation in the medium under study is modeled by the Monte Carlo method combining the calculation of true paths and the use of statistical weights. For the same reason, we represent the surface and interfaces of layers of skin as rough randomly periodic surfaces corresponding to the actual structure of human skin. The method presented can be recommended as a means for the optimum selection of an arrangement for radiation incoupling and outcoupli